Moving xenotransplantation from bench to bedside: Managing infectious risk. Issue 6 (29th July 2022) - Nellore, Anoma; Walker, Jeremey; Kahn, Mauricio J.; Fishman, Jay A.
Abstract : Abstract: Xenotransplantation of organs from swine in immunosuppressed human recipients poses many of the same challenges of allotransplantation relative to the risk for infection, malignancy, or graft rejection in proportion to the degree of immunosuppression and epidemiologic exposures. The unique features of xenotransplantation from pigs relative to infectious risk center on the potential for unusual organisms derived from swine causing productive infection, "xenosis" or "xenozoonosis, " in the host. Based on experience in allotransplantation, the greatest hazard is due to viruses, due to the relative lack of information regarding the behavior of these potential pathogens in humans, the absence of validated serologic and molecular assays for swine‐derived pathogens, and uncertainty regarding the efficacy of therapeutic agents for these organisms. Other known, potential pathogens (i.e., bacteria, fungi, parasites) tend to be comparable to those of humans. Concerns remain for unknown organisms in swine that may replicate in immunosuppressed humans. Clinical trials of genetically modified organs sourced from swine in immunosuppressed humans with organ failure are under development. Such trials require informed consent regarding potential infectious risks to the recipient, determination of breeding characteristics of swine, assessments of potential risks to the public and healthcare providers, consideration of ethical issues posed by this novel therapy, and defined strategies to monitor and address infectious episodes that may be encountered by healthcare teams. Clinical trials in xenotransplantation will allow improved definition of potential infectious risks.